Optical excitation of charge carriers from intra-bandgap states in Ce-doped SnO2 thin films - Silva, Vitor D. L. [UNESP]; Pineiz, Tatiane F. [UNESP]; Morais, Evandro A. [UNESP]; Pinheiro, Marco A. L. [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Saeki, Margarida Juri [UNESP]; Rubo, Elisabete Aparecida Andrello [UNESP] (AIP Publishing, 2008)
Optical excitation of Ce3+-doped SnO2 thin films, obtained by the sol-gel-dip-coating technique, is carried out and the effects on electrical transport are evaluated. Samples are doped with O. lat% of Ce, just above the saturation limit. The excitation is done with an intensity-controlled halogen-tungsten lamp through an interference filter, yielding an excitation wavelength of 513nm, 9 nm wide (width at half intensity peak). Irradiation at low temperature (25K) yields a conductivity increase much lower than above bandgap light. Such a behavior assures the ionization of intra-bandgap defect levels, since the filter does not allow excitation of electron-hole pairs, what would happen only in the UV range (below about 350nm). The decay of intra-bandgap excited levels in the range 250-320 K is recorded, leading to a temperature dependent behavior related to a thermally excited capture cross section for the dominating defect level. © 2008 American Institute of Physics.
Keywords: Cerium; Electroluminescent devices; Thin films; Tin dioxide